Solutions to money laundering prevention through Regulatory Technology (RegTech): Evidence from Islamic and conventional banks - Alivia Meyrizka Utami; Mega Dwi Septivani (Jurnal Ekonomi & Keuangan Islam, 2022)
Purpose – This study aims to examine the effect of the relationship between RegTech and Money Laundering Prevention (MLP). This study also examines the differences between RegTech in Islamic and conventional banks.Methodology – The current study used explanatory research to test hypotheses using primary data obtained through a survey with a questionnaire conducted online with 100 respondents from bank employees, both conventional and Islamic in Indonesia. In addition, an independent t-test was used.Findings – The results reveal that Transaction Monitoring (TM) and Cost and Time (CT) significantly affect MLP, while electronic Know Your Customer (eKYC) does not affect MLP. The comparative test of the differences in RegTech in Islamic and conventional banks confirm differences in transaction monitoring and cost efficiency between Islamic and conventional banks. At the same time, there is no difference in eKYC between Islamic and conventional banks.Originality – Research related to RegTech in Islamic and conventional banks' money laundering prevention efforts is still very limited in Indonesia. This study will contribute to the existing literature on Islamic finance and the development of financial technology in Indonesia.